Novel, Potent and Radio-Iodinatable Somatostatin Receptor 1 (sst(1)) Selective Analogues - Erchegyi, Judit (2009)
The proposed sst(1) pharmacophore1 derived from the NMR structures of a family of mono- and dicyclic undecamers was used to design octa-, hepta- and hexamers with high affinity and selectivity for the somatostatin sst(1) receptor. These compounds were tested for their in vitro binding properties to all five somatostatin (SRIF) receptors using receptor autoradiography; those with high SRIF receptor subtype 1 (sst(1)) affinity and selectivity were shown to be agonists when tested functionally in a luciferase reporter gene assay. Des-AA(1,4-6,10,12,13)-[DTyr(2),DAgl(NMe,2naphthoyl)(8),IAmp(9)]-SRIF-Thr-NH(2) (25) was radio-iodinated ((125)I-25) and specifically labeled sst(1)-expressing cells and tissues. 3D NMR structures were calculated for des-AA(1,4-6,10,12,13)-[DPhe(2),DTrp(8),IAmp(9)]-SRIF-Thr-NH(2) (16), des-AA(1,2,4-6,10,12,13)-[DAgl(NMe,2naphthoyl)(8),IAmp(9)]-SRIF-Thr-NH(2) (23) and des-AA(1,2,4-6,10,12,13)-[DAgl(NMe,2naphthoyl)(8),IAmp(9),Tyr(11)]-SRIF-NH(2) (27) in DMSO. Though the analogues have the sst(1) pharmacophore residues at the previously determined distances from each other, the positioning of the aromatic residues in 16, 23 and 27 is different from that described earlier suggesting an induced fit mechanism for sst(1) binding of these novel, less constrained sst(1)-selective family members.